Performance Analysis of One-Level Signalized Urban Intersections with Exclusive Pedestrian Phases and Diagonal Crossings - Vytautas Grigonis; Vladislav Kondratovič; Vytautas Palevičius; Dainora Juozevičiūtė; Tomas Karpavičius; Juris Smirnovs (The Baltic Journal of Road and Bridge Engineering)
The exclusive pedestrian (hereinafter P) phase with a diagonal crossing is routinely introduced to improve P safety at high-volume intersections. The article analyses and evaluates the feasibility of the exclusive P phase and diagonal crossing at single-level smaller intersections, identifying the advantages and disadvantages of the exclusive P phase and diagonal crossing from the point of view of time losses. In the experimental part, traffic flow modelling is carried out. The traffic flow simulations show that an exclusive P phase is most beneficial in terms of time losses at an intersection with 2+2 lane intersecting streets and ≥ 900 P/hour with ≥ 1600 vehicles/hour (hereinafter V). In addition, an exclusive P phase can be implemented at the small intersections analysed in this paper, where the volume of V is low or medium, regardless of the number of P at the intersection.